2022
DOI: 10.1007/s13304-022-01353-y
|View full text |Cite
|
Sign up to set email alerts
|

Hemopatch® is effective and safe to use: real-world data from a prospective European registry study

Abstract: Surgical procedures are often impeded by bleeding and/or leakage of body fluids. These complications cannot always be resolved by conventional surgical techniques. Hemopatch® is a hemostatic patch that also functions as a sealant. Here we document the effectiveness and safety of Hemopatch® for routine procedures of multiple surgical disciplines. To this end, we performed a prospective, multicenter, single-arm, observational registry study. Patients were eligible if they had received Hemopatch® during an open o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…17-344 dated 11/8/2017). Details of the study design and selection of participants were reported previously [ 15 ]. In brief, the registry was designed as a prospective, multicenter, single-arm, observational study.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…17-344 dated 11/8/2017). Details of the study design and selection of participants were reported previously [ 15 ]. In brief, the registry was designed as a prospective, multicenter, single-arm, observational study.…”
Section: Methodsmentioning
confidence: 99%
“…Perioperative data on the effectiveness and safety of Hemopatch ® as well as the potential use of bicarbonate was recorded with an electronic case report form (eCRF) [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations